SUSTAINABILITY LESSON FROM SOUTHEAST ASIA: SINGAPORE EXPERIENCE - Johannes Widodo (International Journal on Livable Space, 2016)
AbstractTo inaugurate the birth of International Journal on Livable Space (LivaS) it is proper to remind ourselves that livability requires holistic approach, strong vision, sustainable practice, and resilience. This keynote article will outline a story of Singapore, a tiny island nation without natural resources, in its continuous struggle for survival from the past to the present and towards the future. It will discuss various examples on different scale levels (city planning, architecture, design ideas, conservation projects, environmental practices, etc.), and focusing on how our planning and design disciplines can contribute to tangible efforts to achieve environmental, cultural, and economic sustainability in holistic way.